Gadget Addicted Phenomenon In Elementary School Children: Challenges Or Opportunities In Learning? - Linda Feni Haryati; Haryanto Haryanto (UM Purwokerto Press, 2023)
Gadget addiction is characterized by a person's inability to part with the gadget they have. One type of gadget that is used quite massively is the Android mobile phone. The use of mobile phones with all their advanced features has created a new phenomenon at the age of elementary school children called gadget addiction. The number of students who experience this addiction is increasing day by day. Based on this phenomenon, it is necessary to conduct research to find out whether the gadget addiction phenomenon is a challenge or opportunity in learning. This research was designed in the form of library research. The study material in this research is the publication of scientific articles found in national and international journals. The results of the study show that the uncontrolled use of mobile phones on the one hand is a threat, but on the other hand it can actually be used as a support for learning activities. The negative side of uncontrolled use of mobile phones can interfere with mental development, socio-emotional development and can even interfere with students' intellectual development. The positive side of using mobile phones in elementary school-age children is a great opportunity that teachers can use as Android-based learning media. Students who are used to using Android mobile phones are no longer stuttering with technology. Teachers can design educational games based on Android so they don't only access entertainment content on their gadgets. Through educational games students learn more easily so that their enthusiasm for learning increases. Educational games can be developed especially for subjects that have been considered difficult by students such as mathematics. Mobile phones can also be used as a source of knowledge so that students can explore knowledge independently.